STANDARISASI KOMPETENSI AHLI AKUNTANSI SEKTOR PUBLIK - sopian sopian (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2020)
The developments of technology have influenced many professional fields of work including individuals who have public sector accounting education backgrounds. With a qualitative research methodology, the results of the study concluded that standardization of competencies are required by regulations. Two level of competences are medium level (Diploma III) and Bachelor / Applied Bachelor degrees. Qualifications for a 3 year-Diploma are able to master and implement the expertise of the public sector accounting standards with the rules base approach and expertise in using SAKTI Application. Qualifications for the Bachelor / Applied level, an inherent prerequisite is the ability to operate the SAKTI application, and able to implement the expertise of the public sector accounting standards with the principles base approach.